Copyright collective administration in Nigeria : lessons for Africa - Ola, Olukunle (SpringerBriefs in Law, 2013)
This work explores the operation and regulation of copyright collective management in Nigeria. The nexus between creativity and copyright and how creativity has played a pivotal role in development is explained. The need to balance the interests of authors and users is discussed and the societies representing the interest of copyright owners are illustrated. Further, Nigeria's legal framework for collective management is enunciated from a pre-independence and post-independence perspective. In the course of this regulatory challenges encountered in the administration of collective management organizations, steps so far taken to address the problems, legislative reforms and judicial decisions are discussed. A path to the new regime is chartered. The South African Copyright collective management system is explored and a comparison between the Nigerian and South African system is made. Thereby the need for supervisory and regulatory agencies of government is shown to seek the national interest regarding the collective administration of copyright and related rights. Then, suggestions for improvement and lessons for Africa are provided.